Moxibustion for cephalic version: a feasibility randomised controlled trial - Bisits Andrew; Dahlen Hannah; Smith Caroline A; Do Carole K; Schmied Virginia (BMC, 2011)
Abstract Background Moxibustion (a type of Chinese medicine which involves burning a herb close to the skin) has been used to correct a breech presentation. Evidence of effectiveness and safety from systematic reviews is encouraging although significant heterogeneity has been found among trials. We assessed the feasibility of conducting a randomised controlled trial of moxibustion plus usual care compared with usual care to promote cephalic version in women with a breech presentation, and examined the views of women and health care providers towards implementing a trial within an Australian context. Methods The study was undertaken at a public hospital in Newcastle, New South Wales, Australia. Women at 34-36.5 weeks of gestation with a singleton breech presentation (confirmed by ultrasound), were randomised to moxibustion plus usual care or usual care alone. The intervention was administered over 10 days. Clinical outcomes included cephalic presentation at birth, the need for ECV, mode of birth; perinatal morbidity and mortality, and maternal complications. Feasibility outcomes included: recruitment rate, acceptability, compliance and a sample size for a future study. Interviews were conducted with 19 midwives and obstetricians to examine the acceptability of moxibustion, and views on the trial. Results Twenty women were randomised to the trial. Fifty one percent of women approached accepted randomisation to the trial. A trend towards an increase in cephalic version at delivery (RR 5.0; 95% CI 0.7-35.5) was found for women receiving moxibustion compared with usual care. There was also a trend towards greater success with version following ECV. Two babies were admitted to the neonatal unit from the moxibustion group. Compliance with the moxibustion protocol was acceptable with no reported side effects. Clinicians expressed the need for research to establish the safety and efficacy of moxibustion, and support for the intervention was given to increase women's choices, and explore opportunities to normalise birth. The sample size for a future trial is estimated to be 381 women. Conclusion Our findings should be interpreted with caution as the study was underpowered to detect statistical differences between groups. Acceptance by women and health professionals towards moxibustion suggest further research is warranted. Trial Registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12609000985280